A 10-year-old Bangladeshi Girl with Popliteal Pterygium Syndrome: A Case Report (Journal of Surgical Sciences, 2026)
Popliteal pterygium syndrome (PPS) is a unique congenital malformation affecting the limbs, face, and genitalia, named based on the most distinctive feature, the popliteal pterygium. Affecting less than 0.1% of the population, only a few publications have been found on PPS. Despite having no cognitive or systemic dysfunction, the physical features of PPS makes it difficult for the patients to walk or maintain a normal lifestyle. Most of the anomalies in PPS are surgically treatable and therefore, early diagnosis and treatment allows a standard life for the affected. In this report, we present a ten-year-old girl presented with bilateral popliteal pterygium, treated cleft lip, an untreated complete cleft palate and hypoplastic labia majora. Her management approach is furthered discussed in the report.Journal of Surgical Sciences 2023;27(2): 53-56